The Past and present; story of Barong Bangkung - IB Gede Karyambara Putra (Bali Tourism Board, 2018)
On Manis Galungan, the day after Balinese commemorated the triumph of Dharma against Adharma, A group of festively gamelan chimes in accompanying Barong Bangkung, to perform a ritual to ward off negative energy and plague in the village through Ngelawang. Barong Bangkung is an art of dance staged in groups. It consists of approximately twelve people. The dancers are usually boys aged 12-17 years old. Balinese is a cosmocentric society, where they believe Bangkung or Sow, as a manifestation of Lord Shiva in protecting the earth. In its development, the art of Barong Bangkung, as well as Ngelawang, develop not only limited to the art of sacred dance, but also as the performing art. The society conducts Ngelawang by using Barong Bangkung or another holy figure as an expression to worship The God Almighty. As a performing art, the artist does not present a temple’s relic, but a custom-made Barong Bangkung. Usually, the apprentices of the Local school of art seize the opportunity to show their abilities in dance by doing ‘Ngelawang’ on a tourist’s site. Besides to practice their skills, some make it a way to earn some money.